2013
DOI: 10.1097/mib.0b013e3182a3eaeb
|View full text |Cite
|
Sign up to set email alerts
|

Replication Study of Ulcerative Colitis Risk Loci in a Lithuanian–Latvian Case–Control Sample

Abstract: We confirmed the association of the 9 loci (21q21.1, 1p36.13, NKX2-3, MST1, the HLA region, IL10, JAK2, ORMDL3, and IL23R) with UC in the Lithuanian-Latvian population. SNP-SNP interaction analyses showed that the combination of SNPs in the PTPN22 (rs2476601) and C13orf31 (rs3764147) genes increase the risk for UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Similarly, we have recently shown that macrophages and neutrophils from individuals carrying the hypomorphic LACC1 variant Ile254Val (rs3764147) produce less ROS [16]. Interestingly, a SNP-SNP interaction for PTPN22 (rs2476601) and LACC1 (rs3764147) was shown to confer increased risk of UC in a study of Lithuanian and Latvian IBD patients [24], indicating that these two genes may act across overlapping pathogenetic mechanisms of disease predisposition, through neutrophils or macrophage-specific functions.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, we have recently shown that macrophages and neutrophils from individuals carrying the hypomorphic LACC1 variant Ile254Val (rs3764147) produce less ROS [16]. Interestingly, a SNP-SNP interaction for PTPN22 (rs2476601) and LACC1 (rs3764147) was shown to confer increased risk of UC in a study of Lithuanian and Latvian IBD patients [24], indicating that these two genes may act across overlapping pathogenetic mechanisms of disease predisposition, through neutrophils or macrophage-specific functions.…”
Section: Discussionmentioning
confidence: 96%
“…For rs10883365 polymorphism, the pooled ORs were estimated for G versus A, GG versus AA, GA versus AA, dominant model (GG + GA versus AA), and recessive model (GG versus GA + AA). Because of only three studies194950 available for the association between rs11190140 variant and UC risk, we have performed meta-analysis of correlation between rs11190140 polymorphism and CD risk. Subgroup analysis was performed according to ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…The elevated intestinal expression of some genes involved in sphingolipid metabolism was recently reported, prompting exploration of S1P in signaling and subsequent targeting in IBD [77,78]. The authors have studied 13 gene loci that are linked to ulcerative colitis; they found that polymorphism of orosomucoid (ORM) 1-like 3, which is a homologue of the SL regulatory protein ORM1, was associated with UC.…”
Section: Inflammation In Ibd and S1pmentioning
confidence: 99%